ANALISIS KELAYAKAN USAHATANI BAWANG MERAH (ALLIUM ASCALONICUM L) DI KABUPATEN OGAN KOMERING ULU (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2017)
The purpose of this study were (1) To calculate farmer income in onion farming in Ogan Komering Ulu Regency (2) To analyze the feasibility of onion farming in Ogan Komering Ulu Regency. This research was conducted in Ogan Komering Ulu Regency. The determination of the location is done purposively with the consideration that in the District there is only one District that cultivate onion farming as the income of more commercial farmers. The timing of this research is for two months starting from January 2017 until February 2017. The research method used in this research is Case Method and using questionnaire or co-ordinator as a means of collecting data from direct interviews conducted on shallot farmers in Ogan Komering Ulu District. Sampling method used in this research is Saturated Sample method. Where all data is taken all from 1 Sosoh Buay Termap Subdistrict in OKU district because in OKU District there is only one Subdistrict that cultivate onion that is found in Sosoh Buay Termap Subdistrict with total sample 10 sampel. The results showed that onion farming has a R / C value of 3.2. With this calculation, the Red Onion Farming in Tungku Jaya Village Sosoh Buay Termap Sub-district of Ogan Komering Ulu Regency is feasible to be cultivated and developed, because the R / C value>1.